Study ndvB gene expression in Pseudomonas aeruginosa Producing Biofilm (Medico Legal Update, 2021)
Pseudomonas aeruginosa have ability to form biofilm, this biofilm responsible for wide infections andantibiotic resistance development. A novel mechanism to antibiotic resistance mechanisms utilized bybiofilm represented by the presence of ndvB geneencodes a glucosyltransferase enzyme involved in theformation of this glucans, thisglucan mediated sequestration antibiotic away from their cellular targets.In this study was collected 145 samples from burns patients and identification by biochwmicaltsets andVitek-2 compact. The studied the biofilm formation was measured using micro titer plate method we foundthat 49 isolates (100%) of P.aeruginosa were biofilm positive and measured minimal biofilm inhibitoryconcentration(MBIC) of biofilm P.aeruginosa positive biofilmused cefepime as antibiotic was tested usingmicrotiter plate microdilution method (MBIC) values (1gm/ml).Molecular detection of ndvB gene wasmeasured using PCR 100% of isolates were found to contain ndv B gene. Expression of ndvB gene wassignificantly high in biofilm isolates using sub- MBIC values of cefepime. Expression of ndvB gene wassignificantly high in biofilm isolates using glucose with concentration 1% and 2%. This study we concludedbiofilm formation is an important trait of P.aeruginosa that isa cause of antibiotic resistance. ndvB geneexpression responsible for the biofilm resistance mechanism in P. aeruginosa biofilms.